Ice Camp (PRELIMINARY) drift. (GIF). Version 1.0 [PRELIMINARY] ... - Atmospheric Radiation Measurement ARM User Facility; University Of Washington (UCAR/NCAR - Earth Observing Laboratory, 2007)
This data set contains the six hourly record of GPS position and heading from the Ice Station. Data are retrieved from the ARM GPS system and should be considered PRELIMINARY. Period covered from 10/17/97 through the present. The record is updated weekly. ...